Prognostic value of micro-RNA in ovarian cancer: a systematic review and meta-analysis - He, Zhenzhen; Deng, Lihong; Wang, Zhipeng (Frontiers in Oncology, 2026)
BackgroundPrevious studies investigating the association between microRNAs (miRNAs) and ovarian cancer prognosis have yielded inconsistent results. This study aims to synthesize all available evidence through a systematic review and meta-analysis to provide a comprehensive assessment of the prognostic value of miRNAs in ovarian cancer.MethodsA systematic search was conducted in PubMed (from 1965), ISI Web of Science (from 1900), MEDLINE (from 1976), and Scopus (from 1968) through September 9, 2024. Studies published in English, examining the relationship between miRNAs and ovarian cancer prognosis, were included. miRNAs were categorized as upregulated or downregulated based on their expression levels in ovarian cancer tissues compared to normal tissues. The primary outcomes were the hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS) of ovarian cancer patients.ResultsA total of 51 studies involving 6916 ovarian cancer patients and 181 distinct miRNAs were included in the meta-analysis. Upregulated miRNAs were significantly associated with better OS in Chinese ovarian cancer patients compared to patients from other regions (HR 0.43 [95% CI: 0.20-0.65] vs. 1.01 [95% CI: 0.90-1.11], P<0.01). For serous carcinoma, the HR for upregulated miRNAs related to OS was 0.51 (95% CI: 0.11-0.92). Specifically, elevated expression of the miR-200 family was significantly associated with improved OS (HR 0.66 [95% CI: 0.53-0.80]) and PFS (HR 0.68 [95% CI: 0.47-0.89]) in ovarian cancer. Similarly, higher expression of the miR-30 family correlated with improved OS (HR 0.63 [95% CI: 0.39-0.87]) and PFS (HR 0.70 [95% CI: 0.54-0.87]).ConclusionUp-regulated miRNAs show prognostic value in Chinese patients; however, regional influences warrant further investigation. Specifically, miRNAs may serve as important prognostic indicators for serous carcinoma. Different miRNA families, particularly miR-200 and miR-30, have the potential to act as key biomarkers for ovarian cancer prognosis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024579585, identifier CRD42024579585.